Latin American integration and external openness. - Salgado, Germanico (1990)
Notes that there is a new surge towards integration as the region responds to a world that seems to be structuring itself into large economic groupings. Suggests that this would be a good time to study certain programmes on which regional integration could be selectively concentrated, while continuing as far as possible with the reactivation now being intiated.